Liquidity, Volume, and Order Imbalance Volatility - BOGOUSSLAVSKY, VINCENT; COLLIN‐DUFRESNE, PIERRE (Journal of Finance, 2023)
ABSTRACT We examine the dynamics of liquidity using a comprehensive sample of U.S. stocks in the post‐decimalization period. Motivated by a continuous‐time inventory model, we compute a high‐frequency measure of order imbalance volatility to proxy for the inventory risk faced by liquidity providers. We show that high‐frequency order imbalance volatility is an important driver of liquidity and explains the often positive time‐series relation between spread and volume for large stocks, which seems to run counter to most theoretical models. Furthermore, order imbalance volatility is priced in the cross‐section of stock returns.